Childhood maltreatment and depression: mediating role of lifestyle factors, personality traits, adult traumas, and social connections among middle-aged and elderly participants - Xuemei Wang; Zhi Cao; Shaohua Yin; Tingshan Duan; Tao Sun; Chenjie Xu (BMC Medicine)
Abstract Background Accumulating evidence has supported the associations between childhood maltreatment and increased risk of depression; however, the underlying mechanisms remain largely unclear. We aimed to explore the potential role of lifestyle factors, personality traits, adult traumas, and social connections in the association between childhood maltreatment and depression. Methods We used a nationwide cohort data from the UK Biobank, involving half a million participants aged 37–73 years, recruited across 22 centers in the UK between 2006 and 2010. Participants with complete information on childhood experiences and who were free of depression were included. The Childhood Trauma Questionnaire was used to calculate the maltreatment for five subtypes: physical neglect, emotional neglect, sexual abuse, physical abuse, and emotional abuse. Multivariate logistic regression models were implemented to examine the association between childhood maltreatment and depression. A path analysis using structural equation modeling (SEM) was then performed to assess the mediating effects of lifestyle factors, personality traits, adult traumas, and social connections. Results During a mean follow-up of 13.88 years, 5545 participants developed depression. Of the 109,401 participants included in the study (mean [standard deviation] age, 55.75 [7.76] years; 58,315 females [53.30%]), 48,923 participants reported experiencing at least one form of childhood maltreatment. We observed that higher childhood maltreatment scores (odds ratio [OR] 1.28, 95% confidence interval [CI] 1.25–1.31) and all five childhood maltreatment subtypes (physical neglect: 1.46, 1.36–1.56; emotional neglect: 1.78, 1.67–1.89; sexual abuse: 1.48, 1.36–1.61; physical abuse: 1.37, 1.29–1.47; emotional abuse: 1.88, 1.76–2.00) were associated with an increased risk of depression. The SEM results indicated that the effect of childhood maltreatment on depression was partly mediated by lifestyle factors (β − 0.15, P < 0.001), personality traits (β − 0.12, P < 0.001), adult traumas (β 0.50, P < 0.001), and social connections (β − 0.19, P < 0.001), rather than having a direct effect on depression. Conclusions We found that social environmental factors such as lifestyle, personality, adult traumas, and social connections mediate the relationship between childhood maltreatment and depression in middle-aged and elderly people. These findings suggest that addressing these factors may be relevant for mental health interventions in individuals with a history of childhood maltreatment.